On conformal points of area preserving maps and related topics - Albers, Peter; Tabachnikov, Serge (Arxiv, 2022)
In this article we consider area preserving diffeomorphisms of planar domains, and we are interested in their conformal points, i.e., points at which the derivative is a similarity. We present some conditions that guarantee existence of conformal points for the infinitesimal problem of Hamiltonian vector fields as well as for what we call moderate symplectomorphisms of simply connected domains. We also link this problem to the Carath\'eodory and Loewner conjectures.